Bone marrow immunity and myelodysplasia - Claude LAMBERT; Yuenv Wu; Carmen AANEI (Frontiers in Oncology, 2016)
Myelodysplastic syndrome (MDS) is characterized by ineffective hematopoiesis with production of aberrant clones and a high cell apoptosis rate in Bone Marrow (BM). Macrophages are in charge of phagocytosis. Innate Immune cells and specific T cells are in charge of immuno-surveillance. Little is known on BM cell recruitment and activity as BM aspirate is frequently contaminated with peripheral blood. But some evidences suggest an active role of immune cells in protection against MDS and secondary leukemia. BM CD8+CD28- CD57+ T cells are directly cytotoxic and have a distinct cytokine signature in MDS, producing TNF-α, IL-6, CCL3, CCL4, IL-1RA. TNF-α; FAS-L, TRAIL... actively induce apoptosis of aberrant cells. On the other hand, TNF-α has ambiguous activity, increasing MDS related cytopenia and myelofibrosis together with TGF-b. IL-32 amplifies NK cytotoxicity but also the vicious circle of TNF-α production. Myeloid Derived Suppressing Cells (MDSC) are increased in MDS and have ambiguous role in protection/ progression of the diseases. CD33 is expressed on MDS and MDSC cells and is directly involved in MDSC activity. CD33 is a potential target for biotherapy. Other MDS stromal cells have feeding activity and can regulate proliferation too. MDS also has impact on Immunity and can favor chronic inflammation and emergence of auto-immune disorders.